Correlação entre estado nutricional e força de preensão palmar em idosos - Martin, Fabíola Giannattasio [UNIFESP] (2012)
In the aging process, body changes occur, such as reduction of lean mass with impaired muscle strength, affecting the functional capacity. Currently, the Hand Grip Strength Test (HGST) is being used to evaluate the overall muscle strength as an aid in nutritional assessment. OBJECTIVE: To investigate the correlation between the HGST and nutritional status in the elderly. METHODS: Cross sectional study on elderly people attending outpatient of a Federal Public University. To evaluate the nutritional status, were used: body mass index (BMI), nutritional evaluation by Mini Nutritional Assessment (MNA), calf circumference and HGST performed with the aid of a hydraulic hand dynamometer. It was used as reference for the GSTP and the BMI, cutoff points divided by gender (SABE / OPAS Project). RESULTS: The sample was mostly formed (n = 42) by women (66.7%), with an average of 26.82 points in the MNA and BMI, most seniors were eutrophic - 46.4% women and 57.1% men. Men and women were averaged over 31 cm of calf circumference. The average strength for men was higher than women. There was no statistically significant difference between nutritional status classified by BMI and HGST for men and women, there was a statistically significant correlation (p 0.008) between the nutritional status classified by MNA and hand grip strength in the total sample. CONCLUSIONS: Among the methods to assess nutritional status, only MNA correlated positively with the HGST, which is a measure associated with the functionality in the elderly.